STUDIES ON IN-VITRO CULTURING OF BUFFALO (BUBALUS BUBALIS) FETAL FIBROBLAST STEM CELLS - ANJANA, P; KUMANAN, K; PARTHIBAN, M; VIJAYARANI, K; BALASUBRAMANIAM, S (The Indian Journal of Animal Reproduction, 2023)
The present study describes the isolation, in-vitro culturing and characterization of fetal stem cells from buffalo (Bubalus bubalis). During early stages of culture, buffalo fetal fibroblast (BFF) cells had heterogeneous morphology which developed into uniform fibroblast morphology lafer. Single cell derived BFF stem cell (BFFSC) clones were assessed for their osteogenic, chondrogenic and adipogenic potentials using specific differentiation medium. BFFSCs differentiated into osteogenic, chondrogenic and adipogenic lineages as observed by special staining. Total RNA was isolated from BFFSCs and checked for the presence of the three stem cell markers namely, Oct-4, Sox-2 and Nanog, and all three transcription factor genes were detected in differentiated BFFSCs.